Perspectives of the digital methods of diagnosis usage and planning of dental treatment in military field conditions - Rozhko, Mykola; Savchuk, Oleg; Stupnytskyi, Rostyslav; Denga, Anastasia; Stupnytskyi, Illia-Oles (My University, 2024)
The high level of prevalence of dental diseases among servicemen of the Armed Forces of Ukraine requires the introduction of modern types and methods of dental care into the daily practice of military dentists. One option for providing appropriate assistance is the use of digital protocols for diagnosis, treatment planning and treatment of dental pathologies directly in the field or in conditions close to them. As for improving and optimising the provision of dental care in these conditions, it makes sense to complete mobile military dental offices with intraoral scanners and combined additive 3D printers with preliminary training of personnel for their use. Високий рівень розповсюдженості стоматологічних захворювань серед військовослужбовців ЗСУ вимагає впровадження в повсякденну практику військових лікарів-стоматологів сучасних видів і методів стоматологічної допомоги. Одним з варіантів надання відповідної допомоги є застосування цифрових протоколів діагностики, планування лікування і лікування стоматологічних патологій безпосередньо в польових умовах або в умовах, що наближені до них. Стосовно удосконалення та оптимізації надання стоматологічної допомоги в даних умовах, то є сенс комплектувати пересувні військові стоматологічні кабінети інтраоральними сканерами та комбінованими адитивними 3D-принтерами з попереднім навчанням персоналу до їх застосування.
Keywords: military dentistry; військова стоматологія; dental care; стоматологічна допомога; 3D printing; 3D-друк